2023
DOI: 10.1093/eurheartj/ehad121
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in valvular heart disease

Abstract: Valvular heart disease (VHD) is the next epidemic in the cardiovascular field, affecting millions of people worldwide and having a major impact on health care systems. With aging of the population, the incidence and prevalence of VHD will continue to increase. However, VHD has not received the attention it deserves from both the public and policymakers. Despite important advances in the pathophysiology, natural history, management, and treatment of VHD including the development of transcatheter therapies, VHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“… 15 In 2019, it was estimated that 9 million people had moderate-severe AS, a 17-fold increase in the prevalence over the last 30 years. 16 In the PARTNER trial when TAVR was initially examined, the mean age of the patients who could not undergo conventional cardiac surgery was 83 years. 17 Since then, the median age of patients in practice has been between 81 and 84 years.…”
Section: As In Older Adultsmentioning
confidence: 99%
“… 15 In 2019, it was estimated that 9 million people had moderate-severe AS, a 17-fold increase in the prevalence over the last 30 years. 16 In the PARTNER trial when TAVR was initially examined, the mean age of the patients who could not undergo conventional cardiac surgery was 83 years. 17 Since then, the median age of patients in practice has been between 81 and 84 years.…”
Section: As In Older Adultsmentioning
confidence: 99%
“…149 In these VHD centres, the multidisciplinary VHD Heart Teams will evaluate the need, timing, and type of intervention. 16,150 Although, transcatheter TV replacement or repair represent novel and less invasive alternatives to surgery and have shown early promising results, larger randomized studies are needed to define the clinical and procedural endpoints and outcomes, in order to draw more solid conclusions, particularly for the subset of patients presenting with AHF. 151,152 .…”
Section: Tricuspid Regurgitationmentioning
confidence: 99%
“…2,3 Despite the growing epidemic trend and significant disease burden, there are currently no recommended preventive measures effectively thwarting VHD. 4 Compelling evidence supports the role of physical activity in the prevention of atherosclerotic cardiovascular disease and related mortality. 5,6 A recent meta-analysis involving over 30 million participants from 94 prospective cohorts found that adhering to the World Health Organization (WHO) recommendation of 150 minutes per week of moderate-to-vigorous intensity physical activity (MVPA) was associated with a 21% lower risk of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%